2019
DOI: 10.1186/s13075-019-1810-5
|View full text |Cite
|
Sign up to set email alerts
|

Weight loss improves disease activity in patients with psoriatic arthritis and obesity: an interventional study

Abstract: BackgroundObesity is over-represented in patients with psoriatic arthritis (PsA) and associated with higher disease activity, poorer effect of treatment and increased cardiovascular morbidity. Studies on the effects of weight loss are however needed. This study aimed to prospectively study the effects of weight loss treatment with very low energy diet (VLED) on disease activity in patients with PsA (CASPAR criteria) and obesity (body mass index BMI ≥ 33 kg/m2).MethodsVLED (640 kcal/day) was taken during 12–16 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
84
2
6

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(99 citation statements)
references
References 56 publications
7
84
2
6
Order By: Relevance
“…In the present study the weight loss treatment with VLED was judged as easy to implement by most PsA patients, but the transition from VLED to normal food was perceived as harder. [20] A substantial weight reduction was noted during the VLED treatment, but as expected the participants started to gain weight already at six months. The participants were given an energy-reduced dietary advice and were instructed to engage in health-enhancing physical activity at least 150 minutes per week, but no follow up was made between 12-and 24-month visits.…”
Section: Change In Variables Associated With the Metabolic Syndromesupporting
confidence: 56%
See 2 more Smart Citations
“…In the present study the weight loss treatment with VLED was judged as easy to implement by most PsA patients, but the transition from VLED to normal food was perceived as harder. [20] A substantial weight reduction was noted during the VLED treatment, but as expected the participants started to gain weight already at six months. The participants were given an energy-reduced dietary advice and were instructed to engage in health-enhancing physical activity at least 150 minutes per week, but no follow up was made between 12-and 24-month visits.…”
Section: Change In Variables Associated With the Metabolic Syndromesupporting
confidence: 56%
“…We have previously in an open interventional study shown that weight loss treatment with Very Low Energy Diet (VLED) in 41 patients with PsA and obesity resulted in a substantial weight loss of median 18.7 kg (interquartile range: IQR 14.6-26.5) after six months, which was associated with positive effects on the disease activity in joints, entheses and skin. [20] Signi cant improvements were noted regarding number of swollen and tender joints, enthesitis, extent of psoriasis, C-reactive protein (CRP), pain, fatigue and physical function at six months observation. The number of patients with Minimal Disease Activity (MDA) increased from 29% to 54% (p=0.002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The percentage of patients with MDA increased from 29% to 54%. 6 Epidemiological studies have provided robust evidence that obesity is a risk factor for incident psoriasis and PsA, aggravates existing psoriasis and PsA, interferes with treatment of those diseases and is associated with decreased drug survival of biologics in psoriasis. 7,8 Recently published Mendelian randomization studies have provided evidence that higher body mass index (BMI) causally increases the odds of psoriasis by 9% for each unit increase in BMI.…”
Section: Significant Weight Loss Improves and Prevents Psoriasis Andmentioning
confidence: 99%
“…In a recently published prospective cohort study, a 640 kcal per day diet for 12–16 weeks led to a median weight loss of 18·7 kg (18·6% of baseline weight) in 41 out of 46 patients with PsA who completed the study, and was associated with a significant improvement in most disease activity parameters in a dose‐dependent manner. The percentage of patients with MDA increased from 29% to 54% …”
mentioning
confidence: 99%